(untitled) (Global Scientific Review, 2024)
Water is vital for survival, yet polluted water can have negative effects on human health. Many people in underdeveloped nations are still afflicted by the spread of waterborne illnesses, which are made worse by inadequate sanitation and a lack of access to clean water, particularly for drinking. Our goal in compiling this fundamental information from academic sources on water quality treatment and water-borne disease prevention is to help in the creation of a workable plan to deal with the possibility of poor water quality in certain parts of Kirkuk. Improving water quality and creating a healthy environment requires a multi-pronged approach that includes reforming public health institutions, reestablishing monitoring and evaluation systems within competent services, implementing sustainable development techniques, and raising public health awareness and education through media campaigns